Introduction: Philosophers of the World Unite! Theorising Digital Labour and Virtual Work—Definitions, Dimensions, and Forms. (2014) - , Marisol Sandoval, Christian Fuchs, Jernej A. Prodnik, Sebastian Sevignani; Allmer, Thomas
No abstract available